Investigating the Role of Moisture in the Physical Properties of Harra (Terminalia chebula) Fruit - Indu Ganjeer; N. K. Mishra (Emerging Trends in Metabolites, 2025)
Harra (Terminalia chebula) is known as the “king of medicines” in Ayurveda. Its fruits include astringent, purgative, antibacterial, antifungal, and laxative effects. The behavior of harra fruit is mainly dependent on the moisture present. It affects the harvest, post-harvest machinery, separation, packaging, and transportation of harra fruit. This study focused on T’s physical qualities of chebula fresh fruit at 20%–25% (wb) moisture content, such as 50 fruit mass, length, width, thickness, arithmetic-geometric mean diameter, sphericity, surface area, volume, bulk density, true density, porosity, and inclination angle, as engineering properties were 271–290.2 g, 31.91–31.95 mm, 18.43–18.44 mm, 17.34–17.35 mm, 22.70–22.72 mm, 21.69–21.71 mm, 1472.15–1476.44 mm2, 10272.83–10286.01 m3, 581.33–597.84 kg/m3, 1020.73–1098.68 kg/m3, 42.39–46.38%, and 28.78–29.16, respectively. Mechanical properties, such as coefficient of friction were observed on galvanized steel sheet, stainless steel sheet, glass sheet, and mild sheet, as friction coefficients were determined as 0.29–0.31, 0.23-0.24, 0.24-0.25, and 0.28–0.29, respectively. The dried harra fruit must be manually decorated or dehulled in tribal areas by striking it with a stone; this is an extremely labor-intensive and time-consuming process. The study’s physical and mechanical characteristics of T. chebula fruit revealed that, depending on the moisture content, the harra seed can be easily removed from the fruit at a moisture content of 20–25%. Harra fruit which has 20–25% moisture content can be used with machines for embellishment.
Keywords: Bulk density; Harra; Physical properties; Porosity; coefficients of friction